Value creation and the internal goods of business - Bernacchio, Caleb; Couch, Robert (Frontiers in Sociology, 2023)
In his early work, Moore argues that business itself was a MacIntyrean practice. He later rejected this view in response to criticisms from Beadle and others. Most subsequent work, including that of Moore, adopted a view of organizations, including firms, as institutions that house a core practice. We first recount Moore's early view, defend and it from various criticisms. We then briefly review research in management and finance arguing that this research supports a view of business consonant with Moore's early view. Thus, we argue that business is a distinct practice that integrates various productive and auxiliary practices to facilitate mutually beneficial transactions. We conclude by discussing implications of this view, noting that it might be viewed as a classical liberal appropriation of the MacIntyrean framework, and arguing that it poses a challenge to MacIntyreans working with a neo-Aristotelian perspective.